The Role of Antegrade Balloon Aortic Valvuloplasty in a Patient with Low-flow, Low-gradient Aortic Stenosis and ST-elevation Myocardial Infarction - Yoshitomi, Yuki; Watanabe, Yoshikazu; Fujiwara, Takashi; Fujii, Takashi; Shokawa, Tomoki; Akazawa, Ryota; Tsujiyama, Shuji; Maeda, Koji (Journal of Coronary Artery Disease, 2021)
Selecting an appropriate therapeutic strategy for severe aortic stenosis (AS) is challenging in presence of ST-elevation myocardial infarction (STEMI). We report a case in which antegrade balloon aortic valvuloplasty (A-BAV) played an important role in temporizing a patient with severe AS and reduced left ventricular ejection fraction (LVEF) due to STEMI. Our patient was an 85-year-old man who experienced anterior STEMI (peak creatine kinase = 5286 U/L) and fulfilled the criteria of classical LFLG-AS (aortic valve area = 0.68 cm², LVEF = 16%, and MPG = 20 mmHg). He had heart failure symptoms refractory to optimized therapy, including intra-aortic balloon pump (IABP) counterpulsation, even after successful recanalization of the coronary artery. Intervention for severe AS was required; however, the patient was identified to be at high risk for surgery (Society of Thoracic Surgeons score = 16.56%), and our hospital is not a transcatheter aortic valve replacement-capable facility. We performed A-BAV for hemodynamic restoration. A few days after successful A-BAV, tapering of norepinephrine and weaning of IABP were initiated. A cardiac rehabilitation program was initiated during the intensive care period, and which facilitated the patient to be discharged. A-BAV achieved convalescence with no recurrence of heart failure hospitalization at 510 days of follow-up.